2005
DOI: 10.1038/modpathol.3800290
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotyping and p16INK4a expression in cervical intraepithelial neoplasia of adolescents

Abstract: Adolescents have high rates of human papillomavirus (HPV) infection, and persistent high-risk HPV infection can lead to the development of cervical cancer. The cyclin-dependent kinase inhibitor, p16 INK4a is overexpressed in cervical intraepithelial neoplasia (CIN), probably due to a persistent and integrated HPV infection. This study investigated p16 INK4a expression, grades of CIN, and high-risk HPV infection in adolescent cervical biopsies. Biopsies were immunohistochemically stained for p16 INK4a . The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 30 publications
5
51
0
1
Order By: Relevance
“…We found that the distribution patterns of the individual HPV types differed from those shown by a pooled data from North American population and by our previous study in Mississippi, which showed HPV 16 to be the most prevalent, followed by HPV 18 and 31. 8,37 In our current study, HPV 16 was the most prevalent type, followed by HPV 31 and HPV 35. HPV 18 was under-represented in our carcinoma and CIN 2/3 groups.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the distribution patterns of the individual HPV types differed from those shown by a pooled data from North American population and by our previous study in Mississippi, which showed HPV 16 to be the most prevalent, followed by HPV 18 and 31. 8,37 In our current study, HPV 16 was the most prevalent type, followed by HPV 31 and HPV 35. HPV 18 was under-represented in our carcinoma and CIN 2/3 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies confirm p16 overexpression in all HSIL lesions but also in some normal epithelium of cervix at both protein (von Knebel Doeberitz et al, 2002) and messenger levels (Bleotu et al, 2009). On the other hand, p16 is not expressed in cervicitis nor is in squamous metaplasic epithelium (in the absence of CIN stages) (Hu et al, 2005). Still, other studies proved that p16 high level was found in cervical glandular epithelium and also in metaplasic epithelium.…”
Section: Cell Cycle Regulation Markersmentioning
confidence: 89%
“…2,3 Some authors have proposed that p16 INK4a staining could be used to triage women with low-grade cytology results and predict who is more likely to have CIN3 or worse. 4,5 HPV transformed cells with high levels of p16 INK4a can be identified with a protein-based assay. Thus, a biochemical test for p16 INK4a might be better than a test for high-risk HPV DNA at identifying the subset of HPV-infected women with significant clinical disease.…”
Section: Discussionmentioning
confidence: 99%
“…Staining of histology and cytology specimens for p16 INK4a has shown that detection of antibodies to the protein is a sensitive and specific marker of high-grade cervical intraepithelial neoplasia (CIN) and invasive cervical cancer. [2][3][4][5] In a number of studies, p16 INK4a staining of biopsy tissue was seen in over 90% of cases with high-grade CIN and invasive cervical cancer, being generally absent from the normal tissue and staining only zonal or patchy areas of the low-grade CIN cases. 2,6,7 Findings from these immunostaining studies suggest that compared to high-risk HPV DNA, which is detected in the majority of both high-and low-grade lesions, 8 p16 INK4a might be a better marker for identifying those lesions most likely to progress.…”
mentioning
confidence: 99%